2011
DOI: 10.1007/s11032-011-9674-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the Ma locus with pH and titratable acidity in apple

Abstract: Apple fruit flavor is greatly affected by the level of malic acid, which is the major organic acid in mature apple fruit. To understand the genetic and molecular basis of apple fruit acidity, fruit juice pH and/or titratable acidity (TA) were measured in two half-sib populations GMAL 4595 [Royal Gala 9 PI (Plant Introduction) 613988] and GMAL 4590 (Royal Gala 9 PI 613971) of 438 trees in total. The maternal parent Royal Gala is a commercial variety and the paternal parents are two M. sieversii (the progenitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 39 publications
4
98
0
Order By: Relevance
“…Of the four genes in qtl08.3, a 36‐bp insertion 639 bp upstream of the start codon (ATG) of the MdSAUR ‐like gene (MDP0000153382) displayed highly significant distortion of segregation ( P = 1.81 × 10 −20 ) between extremes (high or low) of malate content, so this gene was determined to be a candidate gene in qtl08.3. In addition, MdALMTII (MDP0000252114) in the qtl16.1 region was consistent with a previously reported Ma locus (Xu et al ., ; Ma et al ., 2015b), and the maximum marker segregation distortion ( P = 1.73 × 10 −17 ) between malate content extremities (high or low) was an A/G SNP 2579 bp downstream of the start codon (ATG) in MdALMTII . Therefore, it was also selected as a candidate gene.…”
Section: Resultsmentioning
confidence: 98%
“…Of the four genes in qtl08.3, a 36‐bp insertion 639 bp upstream of the start codon (ATG) of the MdSAUR ‐like gene (MDP0000153382) displayed highly significant distortion of segregation ( P = 1.81 × 10 −20 ) between extremes (high or low) of malate content, so this gene was determined to be a candidate gene in qtl08.3. In addition, MdALMTII (MDP0000252114) in the qtl16.1 region was consistent with a previously reported Ma locus (Xu et al ., ; Ma et al ., 2015b), and the maximum marker segregation distortion ( P = 1.73 × 10 −17 ) between malate content extremities (high or low) was an A/G SNP 2579 bp downstream of the start codon (ATG) in MdALMTII . Therefore, it was also selected as a candidate gene.…”
Section: Resultsmentioning
confidence: 98%
“…The data reported by Xu et al (2012) on desirable and undesirable alleles for the selection of genotypes heterozygous at the Ma locus could be used in conjunction with the data presented here to enable the ideal haplotypes to be selected from a progeny segregating for both levels of fruit titratable acidity and bitter pit incidence. Selection of seedlings associated with elevated levels of certain polyphenolic compounds in progenies also segregating for bitter pit incidence could prove more problematic, since the two loci are tightly linked.…”
Section: Discussionmentioning
confidence: 97%
“…As well as presenting data on the genetics of bitter pit incidence, Kumar et al (2013) also reported significant associations between markers in this region and fruit splitting, and to a lesser extent, internal browning and weighted cortical intensity. Maliepaard et al (1998) first reported the mapping of the Ma locus (controlling fruit pH) to the top of LG16 and the characterization of this locus was performed in greater detail by Xu et al (2012), who performed fine mapping of the region and located the locus in a narrow genetic interval between SSR markers Hi22f06 and Hi02h08, equating to the 4.7 cM of genome immediately flanking the QTL interval identified as containing the Bp-2 locus in this investigation. Recently, the genetic analysis of 17 fruit polyphenolic compounds identified QTLs in seven stable clusters, and identified a major locus controlling the content of flavanols catechin, epicatechin and procyanin B2, and five unknown procyanadim oligomers in the fruit that was located in the region of the bitter pit locus (Chagne et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The profiles of P values, in terms of 2 log 10 (p), for all the tested SNPs for each trait are shown in Fig. explaining 8% variation) on TA resides within the leucoanthocyanidin reductase (LAR1) gene (MDP0000376284) and the next-best SNPs (ss475881686 and GDsnp01588) are located close to the Ma gene (Xu et al, 2012;Khan et al, 2013). Clustering of significant SNPs for OCOL (on LG9) and TA (on LG16) suggested the presence of large-effect quantitative trait locus (QTLs) at these positions.…”
Section: Genome-wide Snp-trait Associationsmentioning
confidence: 99%